1997
DOI: 10.3758/bf03209404
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring source in an unconscious plagiarism paradigm

Abstract: Current laboratory paradigms used to assess unconscious plagiarism consist of three tasks. First, participants generate solutions to a puzzle task with a partner (initial generation task); second, they recall their individual contribution (recall-own task); and third, they attempt to create new solutions that were not offered previously (generate-new task). An analysis of these tasks indicated that they differ in terms of the source monitoring they require. The two generative tasks require less differentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Landau and Marsh (1997) previously claimed that source monitoring in early stages of idea development might obstruct progress because it might inhibit generation of ideas that are similar to, but sufficiently different from, older ideas. They therefore suggested that a creative artist such as a writer might better benefit from source scrutiny once the novel product is finished.…”
Section: Discussionmentioning
confidence: 99%
“…Landau and Marsh (1997) previously claimed that source monitoring in early stages of idea development might obstruct progress because it might inhibit generation of ideas that are similar to, but sufficiently different from, older ideas. They therefore suggested that a creative artist such as a writer might better benefit from source scrutiny once the novel product is finished.…”
Section: Discussionmentioning
confidence: 99%
“…Outside our own previous work, only one previous article has reported recall-own plagiarism rates over 40%. Landau and Marsh (1997) reported two experiments, each with two conditions, using the Boggle task at encoding. Recall-own plagiarism rates ranged from 42% to 56%, thus matching the high levels of plagiarism found here.…”
Section: Discussionmentioning
confidence: 99%
“…However, these rates are inflated when creative tasks are implemented (Marsh & Bower, 1993;Marsh et al, 1997) and when retentionintervals separate generation and testing (Brown & Halliday, 1991). Landau and Marsh (1997) have demonstrated that manipulations can affect plagiarism in the recall-own and generate-new task differently due to different memorial processes being utilised in each. In the generate-new phase, participants need to make a judgement that resembles an old new judgement as they must refrain from presenting an old idea as new.…”
mentioning
confidence: 99%